Prosedur Mekanisme Pembiayaan Investasi Melalui Leasing - Edalmen . (Jurnal Akuntansi, 1999)
Leasing is a agreement between the legal owner of land, property , euipment oe other capital goods (the lessor) and a third party (person or company).